Influence of fat and ionophores on performance of finishing steers - Clary, E.M.; Brandt, Robert T., Jr.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred ninety-two crossbred steers were used in a 2 x 4 factorially arranged experiment to study the effects of including fat and ionophores in finishing rations. Main effects were level of supplemental fat (0 or 4% tallow) and ionophore type [none, Bovatece (B), Rumensine + 'JYlane (RT), or daily rotation of Band RT (BRT)]. Daily feed intake (P<.10) and daily gain (P<.OO5) were reduced for steers fed R'T, but only when fat was included in the diet. In diets containing no supplemental fat, RT increased daily gain 10%. RT improved feed efficiency 8% (P<.05) in nonfat diets, but there was no difference between ionophores in diets containing fat. Adding fat improved feed efficiency of steers fed no ionophore or B. This study suggests that response of finishing steers to ionophores can be modified by the inclusion of fat in the diet.
Keywords: Beef; Ionophores; Fat; Finishing; Performance